Quantification of metabolite concentrations in benign and malignant prostate tissues using 3D proton MR spectroscopic imaging. Issue 4 (24th August 2016) - Weis, Jan; von Below, Catrin; Tolf, Anna; Ortiz‐Nieto, Francisco; Wassberg, Cecilia; Häggman, Michael; Ladjevardi, Sam; Ahlström, Håkan
Abstract : Purpose: To estimate concentrations of choline (Cho), spermine (Spm), and citrate (Cit) in prostate tissue using 3D proton magnetic resonance spectroscopic imaging (MRSI) with water as an internal concentration reference as well as to assess the relationships between the measured metabolites and also between the metabolites and apparent diffusion coefficient (ADC). Materials and Methods: Forty‐six prostate cancer patients were scanned at 3T. Spectra were acquired with the point‐resolved spectroscopy (PRESS) localization technique. Single‐voxel spectra of four healthy volunteers were used to estimate T 1 relaxation time of Spm. Spm, Cho concentrations, and ADC values of benign prostate tissues were correlated with Cit content. Results: The T 1 value, 708 ± 132 msec, was estimated for Spm. Mean concentrations in the benign peripheral zone (PZ) were Cho, 4.5 ± 1 mM, Spm, 13.0 ± 4.4 mM, Cit, 64.4 ± 16.1 mM. Corresponding values in the benign central gland (CG) were Cho, 3.6 ± 1 mM, Spm, 13.3 ± 4.5 mM, Cit, 34.3 ± 12.9 mM. Concentrations of Cit and Spm were positively correlated in the benign PZ zone ( r = 0.730) and CG ( r = 0.664). Positive correlation was found between Cit and Cho in the benign CG ( r = 0.705). Whereas Cit and ADC were positively correlated in the benign PZ ( r = 0.673), only low correlation was found in CG ( r = 0.265). Conclusion: We have shown that it is possible to perform water‐referenced quantitative 3D MRSI of the prostate at the cost of a relatively short prolongation of the acquisition time. The individual metabolite concentrations provide additional information compared to the previously used metabolite‐to‐citrate ratios. Level of Evidence: 1 J. Magn. Reson. Imaging 2017;45:1232–1240